Personalized evidence based medicine: predictive approaches to heterogeneous treatment effects. (10th December 2018) - Kent, David M; Steyerberg, Ewout; van Klaveren, David
Abstract: The use of evidence from clinical trials to support decisions for individual patients is a form of "reference class forecasting": implicit predictions for an individual are made on the basis of outcomes in a reference class of "similar" patients treated with alternative therapies. Evidence based medicine has generally emphasized the broad reference class of patients qualifying for a trial. Yet patients in a trial (and in clinical practice) differ from one another in many ways that can affect the outcome of interest and the potential for benefit. The central goal of personalized medicine, in its various forms, is to narrow the reference class to yield more patient specific effect estimates to support more individualized clinical decision making. This article will review fundamental conceptual problems with the prediction of outcome risk and heterogeneity of treatment effect (HTE), as well as the limitations of conventional (one-variable-at-a-time) subgroup analysis. It will also discuss several regression based approaches to "predictive" heterogeneity of treatment effect analysis, including analyses based on "risk modeling" (such as stratifying trial populations by their risk of the primary outcome or their risk of serious treatment-related harms) and analysis based on "effect modeling" (which incorporates modifiers of relative effect). It will illustrate these approaches with clinical examples and discuss their respective strengths and vulnerabilities.